Comparative effectiveness of intervention components for producing long‐term abstinence from smoking: a factorial screening experiment. (19th November 2015) - Schlam, Tanya R.; Fiore, Michael C.; Smith, Stevens S.; Fraser, David; Bolt, Daniel M.; Collins, Linda M.; Mermelstein, Robin; Piper, Megan E.; Cook, Jessica W.; Jorenby, Douglas E.; Loh, Wei‐Yin; Baker, Timothy B.
Abstract: Aims: To identify promising intervention components that help smokers attain and maintain abstinence during a quit attempt. Design: A 2 × 2 × 2 × 2 × 2 randomized factorial experiment. Setting: Eleven primary care clinics in Wisconsin, USA. Participants: A total of 544 smokers (59% women, 86% white) recruited during primary care visits and motivated to quit. Interventions: Five intervention components designed to help smokers attain and maintain abstinence: (1) extended medication (26 versus 8 weeks of nicotine patch + nicotine gum); (2) maintenance (phone) counseling versus none; (3) medication adherence counseling versus none; (4) automated (medication) adherence calls versus none; and (5) electronic medication monitoring with feedback and counseling versus electronic medication monitoring alone. Measurements: The primary outcome was 7‐day self‐reported point‐prevalence abstinence 1 year after the target quit day. Findings: Only extended medication produced a main effect. Twenty‐six versus 8 weeks of medication improved point‐prevalence abstinence rates (43 versus 34% at 6 months; 34 versus 27% at 1 year; P = 0.01 for both). There were four interaction effects at 1 year, showing that an intervention component's effectiveness depended upon the components with which it was combined. Conclusions: Twenty‐six weeks of nicotine patch + nicotine gum (versus 8 weeks) and maintenance counseling provided by phone are promising intervention components for the cessation and maintenance phases of smoking treatment.